Eugene Dorfman, The narreme in the medieval Romance epic: an introduction to narrative structures. The University of Toronto Press, 1969; xiv + 259 pp. - Perissinotto, Giorgio Sabino Antonio (El Colegio de México, 1971)
Se reseñó el libro: The narreme in the medieval Romance epic: an introduction to narrative structures.